Severe Diabetic Ketoacidosis Complicated by RRT-Requiring Acute Kidney Injury in an Adolescent with Newly Diagnosed Type 1 Diabetes - Putri, Niarsari Anugrahing; Himawan, Indra Widjaja; Utama, Adelia Anggraini (Indonesian Journal of Case Reports, 2025)
Diabetic ketoacidosis (DKA) is a major and potentially life-threatening acute complication of type 1 diabetes mellitus (T1DM), particularly in children and adolescents. We report a 17-year-old male who presented with severe DKA as the first manifestation of previously undiagnosed T1DM. On admission, he was profoundly acidotic, markedly hyperglycemic, hemodynamically unstable, and anuric, with rising creatinine levels. Despite appropriate resuscitation and standard DKA therapy, renal function deteriorated to stage 3 AKI according to KDIGO, leading to the initiation of renal replacement therapy. During the initial phase of dialysis, the patient experienced several episodes of hypoglycemia, requiring insulin dose adjustment and closer glucose monitoring. Renal function gradually improved and patient was discharged in stable condition. This case highlights that DKA as the initial presentation of type 1 DM in adolescents can progress to severe AKI requiring dialysis, and emphasizes the importance of careful monitoring of renal function and glycemic management during renal replacement therapy in pediatric patients.